Radio Receivers for Systems of Fixed and Mobile Communications - Logvinov, Vasiliy V.; Smolskiy, Sergey M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The textbook acquaints the reader with the architecture of receivers of analog and digital radio systems, helps to study the stages of designing a modern radio receiver and reveals the reasons and methods for its effective operation in networks for various purposes. Particular attention is paid to the methods of generating and processing signals in the receivers of digital systems with multiple access, which make it possible to provide data transfer rates close to the maximum possible (according to Shannon). As a textbook for students studying methods of optimal signal reception, the book will also be useful to specialists in the field of telecommunications involved in the development of radio receivers. The book shows how the development of theoretical, circuitry and integrated technologies led to the active introduction of algorithmic methods for signal processing changed both the design of receivers and the methods of forming the information flow in free space (MIMO, beamforming). The creation of a global 5G network based on heterogeneous networks puts forward new requirements for the architecture of receivers, which are determined by the requirements to achieve high data rates, low time delays or use in networks with coordinated multipoint transmission and reception (CoMP). To consolidate the knowledge gained, the book includes a complete set of materials for online classes, including questions and answers, a guide to solving problems for each chapter, and computer modeling units of receivers in the MicroCAP environment, based on preliminary calculations.
Chapter 1. Radio Systems and Radio Signals -- Chapter 2. Systems and Networks of Wireless Communications -- Chapter 3. Architectures of Modern Radio Receivers -- Chapter 4. Noise Immunity of Radio Receivers -- Chapter 5. Technical Indicators of Devices for Radio Signal Reception and Processing -- Chapter 6. The MicroCAP12 System for Circuit Modeling.
Keywords: Telecommunication; Electronic circuits; Measurement; Measuring instruments; Communications Engineering, Networks; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems; Measurement Science and Instrumentation; Radio -- Receivers and reception -- Design and construction; Signal detection